Extracranial and Intracranial Vasculopathy With “Moyamoya Phenomenon” in Association With Alagille Syndrome - Delaney, Siobhan; O'Connor, Ged; Reardon, William; Murphy, Stephen J. X.; Tierney, Sean; Ryan, Barbara M.; Delaney, Holly; Doherty, Colin P.; Guiney, Michael; Brennan, Paul; Tobin, W. Oliver; McCabe, Dominick J. H. (Frontiers in Neurology, 2019)
Background: Alagille syndrome (AGS) is an autosomal-dominant, multisystem disorder caused by mutations in the JAG1 gene. Case description: A 34-year-old man was referred to our service 10 years ago with focal seizures with impaired awareness and transient slurred speech. He had a 5-year history of intermittent left monocular low-flow retinopathy. He has a family history of AGS. General examination revealed mild hypertension, aortic regurgitation and livedo reticularis. Neurological examination was normal. Investigations: He had mild hyperlipidaemia and persistently-positive lupus anticoagulant consistent with primary anti-phospholipid syndrome. Colour Doppler ultrasound revealed low velocity flow in a narrowed extracranial left internal carotid artery (ICA). MR and CT angiography revealed a diffusely narrowed extracranial and intracranial left ICA. Formal cerebral angiography confirmed severe left ICA narrowing consistent with a left ICA ‘vasculopathy’ and moyamoya phenomenon. Transthoracic echocardiogram revealed a bicuspid aortic valve and aortic incompetence. Molecular genetic analysis identified a missense mutation (A211P) in exon 4 of the JAG1 gene, consistent with AGS. Discussion: AGS should be considered in young adults with TIAs/stroke and unexplained extracranial or intracranial vascular abnormalities, and/or moyamoya phenomenon, even in the absence of other typical phenotypic features. Gene panels should include JAG1 gene testing in similar patients.